Pricing and reimbursement mechanisms for advanced therapy medicinal products in 20 countries - Rejon-Parrilla, Juan Carlos; Espin, Jaime; Garner, Sarah; Kniazkov, Stanislav; Epstein, David (Frontiers in Pharmacology, 2023)
Introduction Advanced Therapy Medicinal Products (ATMPs) are a type of therapies that, in some cases, hold great potential for patients without an effective current therapeutic approach but they also present multiple challenges to payers. While there are many theoretical papers on pricing and reimbursement (P&R) options, original empirical research is very scarce. This paper aims to provide a comprehensive international review of regulatory and P&R decisions taken for all ATMPs with centralized European marketing authorization in March 2022. Methods A survey was distributed in July 2022 to representatives of 46 countries. Results Responses were received from 20 countries out of 46 (43.5%). 14 countries reimbursed at least one ATMP. Six countries in this survey reimbursed no ATMPs. Conclusion Access to ATMPs is uneven across the countries included in this study. This arises from regulatory differences, commercial decisions by marketing authorization holders, and the divergent assessment processes and criteria applied by payers. Moving towards greater equality of access will require cooperation between countries and stakeholders, for example through the WHO/Europe Access to Novel Medicines Platform.